2022
DOI: 10.1007/s40544-021-0551-z
|View full text |Cite
|
Sign up to set email alerts
|

In-situ TEM studies on stick-slip friction characters of sp2 nanocrystallited carbon films

Abstract: Carbon films with two different kinds of sp2 nanocrystallited structure were investigated to study the stick-slip friction with the in-situ and ex-situ tests. In-situ transmission electron microscope (TEM) observation and nanofriction tests revealed that the origins of stick and slip varied with shear stress and film deformation. At the stick stage, shear stress gradually increased with the contact strengthened until reached the shear strength to break the interfacial adhesion; at the slip stage, the shear str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 50 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…However, due to the structural characteristics of graphene, friction studies for graphene are mainly at the nanoscale. As the research scale becomes smaller, the details of friction changes are more prominent, and many friction behaviors that cannot be observed in macroscopic friction are found. , Among them, the stick–slip behavior is a common phenomenon in graphene nanofriction, and scholars have proposed the P–T model to explain this behavior . In the nanofriction of graphene on a silicon oxide substrate, Lee et al first observed the friction-strengthening behavior of graphene in experiments and proposed the fold theory to explain this behavior.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the structural characteristics of graphene, friction studies for graphene are mainly at the nanoscale. As the research scale becomes smaller, the details of friction changes are more prominent, and many friction behaviors that cannot be observed in macroscopic friction are found. , Among them, the stick–slip behavior is a common phenomenon in graphene nanofriction, and scholars have proposed the P–T model to explain this behavior . In the nanofriction of graphene on a silicon oxide substrate, Lee et al first observed the friction-strengthening behavior of graphene in experiments and proposed the fold theory to explain this behavior.…”
Section: Introductionmentioning
confidence: 99%